INFLUENCE of inhalation coal and rock dust on morphological changes of heart muscle (experimental research) - N. N. Mikhaylova; M. S. Bugaeva; O. I. Bondarev (Acta Biomedica Scientifica)
Early stages of coal-dust exposure on laboratory animals do not cause morphological changes in heart muscle. Later periods (6—9 weeks of experiment) are accompanied on the one hand expressed compensatory-adaptive processes, on the other hand. - selective accumulation of lipofuscin in cardiomyocytes. Accumulation of lipofuscin is directly dependent on the duration of the adverse effects of the dust factor and. may be one of the main morphological markers of deep damage and cell death with prolonged exposure to coal and rock dust.